Educators' perceptions of responsibility-sharing in feedback processes. Issue 1 (2nd January 2021) - Winstone, Naomi; Pitt, Edd; Nash, Robert
Abstract: Many policies and processes in higher education reinforce a conception of feedback as being the transmission of information, thus placing primary responsibility on educators for delivering this information 'well' whilst neglecting the essential responsibilities of learners. In this study, 216 university educators described the responsibilities of students, and of educators themselves, in the feedback process. We analysed their responses using both content analysis and a novel linguistic analysis of the specific words used. The content analysis indicated a clear influence of transmission-based models of feedback on educators' views, with educators seen as responsible primarily for providing comments, and students responsible primarily for processing these comments. Linguistically, educators conveyed greater certainty and were more likely to use referents to power and positive emotion, when describing their own as opposed to students' responsibilities. These findings underscore the necessity of a cultural shift toward responsibility-sharing in the context of feedback in higher education.